2011
DOI: 10.1002/rcs.398
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and pathological outcomes after right hemicolectomy: case‐matched study comparing robotic and open surgery

Abstract: Robotic right hemicolectomy is an oncologically safe and effective procedure. The number of lymph nodes retrieved in the robotic group compared with the open group of our series was more homogeneous, and none of the patients operated on with this technique had a suboptimal lymphadenectomy. Further clinical trials are needed to confirm current evidence and determine whether this can influence the prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 21 publications
(25 reference statements)
0
9
1
Order By: Relevance
“…Several other authors have also reported their early assessment of da Vinci Ò robotic colorectal surgery [93][94][95][96][97][98]. Although some variability exists, the early phases of robotic literature generally revealed similar conclusions showing comparable short-term results compared with laparoscopy with lower blood loss, and increased length of surgery and cost [99,100].…”
Section: Colorectal Surgerymentioning
confidence: 85%
“…Several other authors have also reported their early assessment of da Vinci Ò robotic colorectal surgery [93][94][95][96][97][98]. Although some variability exists, the early phases of robotic literature generally revealed similar conclusions showing comparable short-term results compared with laparoscopy with lower blood loss, and increased length of surgery and cost [99,100].…”
Section: Colorectal Surgerymentioning
confidence: 85%
“…This holds true for robotic right colectomy for colon cancer as well. 11 However, length of hospital stay was comparable between robotic and laparoscopic right colectomy. 9,12 In addition, robotic right colectomy provides similar overall morbidity and mortality rates with open 11 and conventional laparoscopic right colectomy.…”
Section: Robotic Right Colectomy For Cancermentioning
confidence: 88%
“…9 Similarly, robotic right colectomy was associated with a longer operating time than open right colectomy for colon cancer. 11 However, the study comparing the first 30 laparoscopic and robotic right colectomies of the same surgeon and institute suggested statistically comparable operating times for both the groups. 12 Previous studies, including patients with both benign and malign disease, reported either prolonged 16 or comparable 17 operating times for robotic right colectomy.…”
Section: Robotic Right Colectomy For Cancermentioning
confidence: 94%
See 2 more Smart Citations